IN VITRO ANTIFUNGAL SENSITIVITY OF FLUCONAZOLE, CLOTRIMAZOLE AND NYSTATIN AGAINST VAGINAL CANDIDIASIS IN FEMALES OF CHILDBEARING AGE - Khan, Fouzia; Baqai, Rakhshanda (Journal of Ayub Medical College Abbottabad, 2010)
Background: Vaginal candidiasis is the most common infection of females. A large variety of antifungal drugs are used for treatment. The objective of this study was isolation and identification of Candida from high vaginal swabs and in vitro antifungal activity of Clotrimazole, Fluconazole and Nystatin against Candida. Methods: Two hundred and fifty high vaginal swabs were collected from females reporting at different hospitals of Karachi. Wet mount was performed to observe the budding cells of Candida. Vaginal swabs were cultured on Sabouraud’s dextrose agar with added antibiotics. Plates were incubated at room temperature for seven days. Chlamydospores of Candida albicans were identified on corn meal agar. Species of Candida were identified on Biggy agar. In vitro antifungal activity of Clotrimazole, Fluconazole and Nystatin was performed by MIC (Minimum inhibitory concentration), well diffusion method and disc diffusion method. Results: Out of 250 high vaginal swabs, Candida species were isolated in 100 (40%) of cases. Out of 100, C. albican 30 (30%), C. tropicalis 21 (21%), C. parapsillosis 10 (10%), C. parakrusi 8 (8%), C.glabrata 8 (8%), C. krusei 3 (3%) were isolated. In vitro antifungal activity indicated Clotrimazole (MIC 16 and 8 µg/ml) effective against 68 (70%) of Candida SPP, Fluconazole (MIC 64 and 32 µg/ml) effective against 29 (36.2%) and Nystatin disc (100 units) was 51 (63.5%) effective. Conclusion: C. albicans was mainly isolated. Clotrimazole was more effective as compared to Fluconazole and Nystatin. Antifungal susceptibility testing should be determined before therapy to avoid treatment failures. Keywords: Vaginal candidiasis, Antifungal sensitivity, Species of Candida